Bilineage T-lymphoblastic/myeloid extramedullary blast crisis in chronic myelogenous leukemia - Indu M Nair; M Feroze; K P Aravindan (Wolters Kluwer Medknow Publications, 2016)
The blast crisis of chronic myelogenous leukemia (CML) can be hematological or extramedullary. About 25% of these cases fulfill the criteria for mixed phenotype acute leukemia. We here report a case of a second blast crisis of CML which was extramedullary and was immunophenotypically bilineage T/myeloid.